First Morning Pregnanetriol and 17-Hydroxyprogesterone Correlated Significantly in 21-Hydroxylase Deficiency - Itonaga, Tomoyo; Izawa, Masako; Hamajima, Takashi; Hasegawa, Yukihiro (Frontiers in Endocrinology, 2022)
Background Biochemically monitoring 21-hydroxylase deficiency (21-OHD) is challenging. Serum/blood 17-hydroxyprogesterone (17OHP) measurements are normally used for this purpose. Urinary pregnanetriol (PT), a urinary metabolite of 17OHP, may also be used. Based on auxological data, we previously reported that the optimal first morning PT value fell in the range of 2.2–3.3 mg/gCr (95% confidence interval of the mean) and 0.59-6.0 mg/gCr (10th – 90th percentile) for monitoring 21-OHD treatment. No report thus far has directly compared the first morning urinary PT value with the 17OHP value at various times during the day. Objective To explore the correlation between the first morning urinary PT value before glucocorticoid administration and the serum/blood 17OHP value at three time points, namely, before and two and four hours after glucocorticoid administration. Design This was a prospective study done at two children’s hospitals. Methods In total, 25 patients with 21-OHD aged 3-25 years were recruited. Their urinary PT levels and 17OHP levels were measured for three days within a total period of one week. The first morning PT value was collected on all three days. Dried blood spots and serum were used to measure 17OHP. Results The range for the first morning PT value for all the samples (n=69) was 0.10-56.1 mg/gCr. A significant, positive correlation was found between the first morning PT and 17OHP values before medication (r=0.87, p<0.01), and weaker correlation was observed between the first morning PT and 17OHP values after medication. Conclusions The first morning PT correlated more significantly with 17OHP before the morning medication. Measuring the first morning PT value may be more practical and useful for monitoring 21-OHD biochemically.